Замыкающий: [повести] / Валентина Сидоренко - Сидоренко Валентина Николаевна (Сибириада, 2018)
Экземпляры: ЦБ (20191004) / Инвентарный номер: 51383 / Цена: 261.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 34 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6